2024
DOI: 10.1038/s41375-024-02159-0
|View full text |Cite|
|
Sign up to set email alerts
|

Dose modification dynamics of ponatinib in patients with chronic-phase chronic myeloid leukemia (CP-CML) from the PACE and OPTIC trials

Elias Jabbour,
Jane Apperley,
Jorge Cortes
et al.

Abstract: Ponatinib, the only approved all known-BCR::ABL1 inhibitor, is a third-generation tyrosine-kinase inhibitor (TKI) designed to inhibit BCR::ABL1 with or without any single resistance mutation, including T315I, and induced robust and durable responses at 45 mg/day in patients with CP-CML resistant to second-generation TKIs in the PACE trial. However, cardiovascular toxicities, including arterial occlusive events (AOEs), have emerged as treatment-related AEs within this class of TKIs. The OPTIC trial evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…At both 12-month and 36-month time points, the 45 mg QD dose strategy with a reduction to 15 mg QD upon reaching MR 2 displayed the most optimal benefit-to-risk ratio [98,100]. Overall, a comparison study found that patients from the OPTIC trial had lower incidences of adverse effects compared to patients from the PACE trial and highlighted the benefits of dose optimization strategies for TKIs [101] It has previously been reported that in a phase I/II clinical study, DA could be combined with the hypomethylating agent, decitabine, to effectively treat advanced phase CML (CML-AP, CML-BP) [102]. Furthermore, it has been shown that the anti-apoptotic BCL-2 family proteins are upregulated in CML blast crisis cells and LSCs via BCR::ABL1 signaling, and preclinical studies combining TKIs with the BCL-2 inhibitor venetoclax revealed synergistic anti-leukemic effects in BCR::ABL1 + myeloid leukemias [103,104].…”
Section: Pace and Opticmentioning
confidence: 96%
See 1 more Smart Citation
“…At both 12-month and 36-month time points, the 45 mg QD dose strategy with a reduction to 15 mg QD upon reaching MR 2 displayed the most optimal benefit-to-risk ratio [98,100]. Overall, a comparison study found that patients from the OPTIC trial had lower incidences of adverse effects compared to patients from the PACE trial and highlighted the benefits of dose optimization strategies for TKIs [101] It has previously been reported that in a phase I/II clinical study, DA could be combined with the hypomethylating agent, decitabine, to effectively treat advanced phase CML (CML-AP, CML-BP) [102]. Furthermore, it has been shown that the anti-apoptotic BCL-2 family proteins are upregulated in CML blast crisis cells and LSCs via BCR::ABL1 signaling, and preclinical studies combining TKIs with the BCL-2 inhibitor venetoclax revealed synergistic anti-leukemic effects in BCR::ABL1 + myeloid leukemias [103,104].…”
Section: Pace and Opticmentioning
confidence: 96%
“…At both 12-month and 36-month time points, the 45 mg QD dose strategy with a reduction to 15 mg QD upon reaching MR 2 displayed the most optimal benefit-to-risk ratio [ 98 , 100 ]. Overall, a comparison study found that patients from the OPTIC trial had lower incidences of adverse effects compared to patients from the PACE trial and highlighted the benefits of dose optimization strategies for TKIs [ 101 ].…”
Section: Tki Treatment Strategies In the Clinicmentioning
confidence: 99%
“…In the OPTIC trial, which assessed ponatinib starting doses of 45, 30, and 15 mg QD, 51.6%, 35.5%%, and 25.3%, respectively, of patients with T315I-mutated CML-CP achieved BCR::ABL1 on the International Scale (IS) ≤1% by 12 months (predictive of long-term survival) [ 1 , 16 , 19 , 20 ]. Safety concerns associated with ponatinib include the risk of cardiovascular (CV) adverse events (AEs), including arterial occlusive events (AOEs), in 14% to 31% of patients with CML-CP, although rates can be reduced by approximately 60% using response-based dose-reduction strategies [ 1 , 13 , 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…9,11 Subsequent studies of ponatinib in both chronic myeloid leukemia and Ph+ ALL used a response-based dose-reduction strategy to improve the risk-benefit ratio. 11,12 But whether these riskreduction strategies and increased tyrosine kinase inhibitor potency will translate to an improved outcome for ponatinib vs imatinib in Ph+ ALL is the question that PhALLCON aims to address.…”
mentioning
confidence: 99%
“…However, ponatinib has also been associated with increased vascular toxicity, particularly in patients who received higher doses for longer periods. 12 These arterial occlusive events have plagued prior ponatinib trials, leading to temporary withdrawal of ponatinib from the market and a black box warning. Arterial occlusive events were the main reason for early termination of the frontline ponatinib vs imatinib phase 3 randomized trial in chronic myeloid leukemia, which treated patients with 45 mg once daily of ponatinib.…”
mentioning
confidence: 99%